Adverse Effects of Saccharum offi cinarum Molasses on Rat Testicular Cells - Eunice Ogunwole; Olufadekemi T Kunle-Alabi; Opeyemi O Akindele; Yinusa Raji (Advances in Toxicology and Toxic Effects - Peertechz Publications, 2019)
Introduction: Saccharum offi cinarum is the source of the popularly used refi ned sugar, with reported anti-androgenic effects. Saccharum offi cinarum Molasses (SOM), a sweet byproduct obtained during sugar production, rich in phenolic compounds, minerals and organic acids is being explored as a substitute sweetener for refi ned sugar due to its nutritional advantage. However, paucity of knowledge of its effects on reproductive functions prompts this study designed to assess activities of testicular cells cultured in SOM fractions. Methods: Blackstrap® Saccharum offi cinarum molasses was fractionated using methanol and water. Constituents of SOM methanol (SOMMF)and aqueous fractions (SOMAqF) were identifi ed using Gas Chromatography Mass Spectrometry. Testicular cells from twelve rats were isolated, cultured and incubated with SOMMF, SOMAqF, components of SOMMF (Lupeol) and SOMAqF (Diethyl Phthalate). Cell viability, proliferation and testosterone biosynthesis were quantifi ed using MTT assay and ELISA. Data were analyzed using ANOVA at p<0.05.